Earnings management and the market performance of acquiring firms - Louis, Henock (Journal of Financial Economics, 2004)
I examine the market's efficiency in processing manipulated accounting reports and provide an explanation for the post-merger underperformance anomaly. I find strong evidence suggesting that acquiring firms overstate their earnings in the quarter preceding a stock swap announcement. I also find evidence of a reversal of the stock price effects of the earnings management in the days leading to the merger announcement. However, the pre-merger reversal is only partial. I find evidence of a post-merger reversal of the stock price effects of the pre-merger earnings management. The results suggest that the extant evidence of post-merger underperformance by acquiring firms is partly attributable to the reversal of the price effects of earnings management. The study also suggests that the post-merger reversal is not fully anticipated by financial analysts in the month immediately following the merger announcement. However, consistent with suggestions in the financial press that managers guide analysts’ forecasts to “beatable” levels, the effect of the earnings management reversal seems to be reflected in the consensus analysts’ forecasts by the time of the subsequent quarterly earnings releases.